Decision factors for remote work adoption: A critical analysis - Ferreira, Rafael Cardoso de Figueiredo Rodrigues (2021)
Remote Work adoption is increasing among organizations. For economic reasons, competitive advantage or even as part of the business continuity plan, Remote Work is a domain worth of further investigation. However, the literature lacks further insights and consensus regarding the decision factors that organizations may consider before and during Remote Work adoption. Design Science Research Methodology was adopted. A thorough and rigorous Systematic Literature Review was performed to elicit the main decision factors (Advantages, Disadvantages, Challenges and Driving Forces) and their relation that influence the Remote Work adoption and its implementation. Plus, a conceptualization of Remote Work domain is presented, and the main decision factors were investigated. A list for each decision factor as well as how they relate among them is also presented and a critical analysis performed. Dozens of factors were identified and related. Those were proven to be extremely important to consider before any Remote Work adoption. This research is a strategic tool for organizations willing to implement Remote Work and a base for further academic developments in the field. In the extent of its complexity, researches from other fields (team management, governance, business process management, among others) are incentivized so valuable inputs may be provided and complement the field.